Toward Evidence-Based Practice. Issue 1 (January 2021) - Rohan, Annie J.; Giurgescu, Carmen; Heck, Jennifer L.; O'Brien-Abel, Nancy
Abstract : Experts suggest how 6 research articles can be used in nursing practice.